The Eocene-Oligocene Nanchititla dike swarm, eastern Michoacán, México. Issue 2 (9th December 2020) - Chávez-Álvarez, María Jazmín; Cerca, Mariano; López Martínez, Margarita; Origel-Gutiérrez, Gabriel; Ferrari, Luca
ABSTRACT: We present a geologic map for the Eocene-Oligocene Nanchititla mafic dike swarm consisting of over 140 NNW-SSE trending dike segments; whose emplacement was influenced by the left-lateral transtensional deformation regime prevailing in southern México during the Cenozoic. The hosting rock is a mechanically heterogeneous continental sedimentary sequence interbedded with volcanic rocks. Interaction among magma and host rock promoted the formation of dike-sill systems, segmentation and sinuous intrusions. Dike thickness observed is between 1 and 45 m with a peak in the range from 1 to 5 m. Six giant dikes of more than 30 m thick were documented. The 80% of the dikes have porphyritic textures rich in plagioclase phenocrysts with size ranging from 0.5 to 2.5 cm. New and compiled 40Ar-39Ar ages constrain the swarm emplacement between 30 and 34.5 Ma, whereas plagioclase phenocrysts entrained by the magma have older ages between 35 and 42 Ma.